Critical success in e-learning : an examination of technological and institutional support factors - Masrom, Maslin; Zainon, Othman; Rahiman, Rosdina (Academy of Taiwan Information Systems Research, 2008)
In recent years, information technology (IT) has become prominent to support teaching and learning activities. IT tools allow us to create, collect, store and use information and knowledge. E-learning was one of the IT tools introduced at College of Science and Technology (CST), University Technology Malaysia (UTM) Kuala Lumpur since 2001. It has enabled a paradigm shift from institution-centered instruction to anywhere, anytime and anybody learning models. In CST the e-learning technology was used for accessing the syllabus and course content, submitting assignments, and taking class quizzes. This paper focuses on issues relating to the e-learning critical success factors (CSFs) from the university students’ perspective. In this study, two main factors related to the e-learning CSFs within a university environment including technological and institutional support factors were examined. The confirmatory factor modeling approach was used to assess the criticality of the measures included in each factor. The results indicated that the most critical measures for technological factor in terms of ease of access and infrastructure are the browser efficiency, ease of use of course website and computer network reliability. Meanwhile, for institutional support factor, the most critical measure is the availability of technical support or help desk.